Subsynaptic Domains in Super-Resolution Microscopy: The Treachery of Images - Yang, Xiaojuan; Specht, Christian G. (Frontiers in Molecular Neuroscience, 2019)
The application of super-resolution optical microscopy to investigating synaptic structures has revealed a highly heterogeneous and variable intra-synaptic organization. Dense subsynaptic protein assemblies named subsynaptic domains or SSDs have been proposed as structural units that regulate the efficacy of neuronal transmission. However, an in-depth characterization of subsynaptic domains has been hampered by technical limitations of super-resolution microscopy of synapses, namely the stochasticity of the signals during the imaging procedures and the variability of the synaptic structures. Here, we synthetize the available evidence for the existence of subsynaptic domains at central synapses, as well as the possible functional relevance of SSDs. In particular, we discuss the possible regulation of co-transmission at mixed inhibitory synapses as a consequence of the subsynaptic distribution of glycine receptors (GlyRs) and GABAA receptors (GABAARs).